Development and optimisation of a novel three‐way extraction technique based on a combination of Soxhlet extraction, membrane assisted solvent extraction and a molecularly imprinted polymer using sludge polycyclic aromatic hydrocarbons as model compounds. Issue 4 (27th December 2017) - Ncube, Somandla; Lekoto, Goitsemang; Cukrowska, Ewa; Chimuka, Luke
Abstract: A novel technique that integrates extraction and clean‐up into a single step format is reported as part of the search for new sample preparation techniques in the analysis of persistent organic pollutants from complex samples. This was achieved by combining the extraction efficiency of the Soxhlet extractor, the selectivity of a size exclusion membrane and the specificity of a molecularly imprinted polymer for the extraction of polycyclic aromatic hydrocarbons from wastewater sludge followed by quantitation using gas chromatography with time‐of‐flight mass spectrometry. The approach is described as the Soxhlet extraction membrane‐assisted solvent extraction molecularly imprinted polymer technique. This technique was optimised for various parameters such as extraction solvent, reflux time and membrane acceptor phase. The applicability of the developed technique was optimised using a wastewater sludge certified reference material and then tested on real wastewater sludge samples. The method detection limits ranged from 0.14 to 12.86 ng/g with relative standard deviation values for the extraction of the 16 US‐EPA priority polycyclic aromatic hydrocarbons from wastewater sludge samples ranging from 0.78 to 18%. The extraction process was therefore reproducible and showed remarkable selectivity. The developed technique is a promising prospect that can be applied in the analysis of organic pollutants from complex solid samples.